Behaviour of pinned beam-to-column connections for precast concrete frames - Chan, Dennis Paul Leong (2006)
The connection design plays a vital role in determining the successful of the precast concrete structure. The detailing and structural behaviour of the connection such as beam-to-column connections will affect the strength, stability and constructability as well as load distribution of the structure under load. However, lack of experimental data and analytical proof accounts for the ductile connection details for beam-to-column connections are major problems in precast concrete structure. Reliable connection behaviour can only be properly assessed by laboratory testing or proven performance. Therefore, in this research project, laboratory testing was conducted to determine the moment of resistance of beam-to-column connections and to study the behaviour of beam-to-column connections in precast concrete frames. This research project involved a total of four specimens which was limited to simple beam-to-column connections in precast concrete frames. At the end of research, it is found that the performance of precast concrete simple beam-to-column connection had been improved using top fixing angle cleats. Furthermore, ductility of connection was not significantly reduced after this modification.